MEMBIASAKAN TRADISI AGAMA: ARAH BARU PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 3 YOGYAKARTA - Moch Fuad (Jurnal Pendidikan Agama Islam, 2017)
This study was aimed to describe: (1) the learning process of PAI based on the culture and character of the nation in SMA Negeri 3 Yogyakarta, (2) the reform of model and contextualization of the material (integrated domain) by PAI teacher, (3) reveals the model reformation and material contextualization (Integrated domain) conducted by PAI teachers can improve the domain of knowledge, attitudes and behavior of students, (4) the practice of practicing the students in school and at home. Research on "Familiarize the Religious Tradition in School" held by SMA Negeri 3 in Yogyakarta using qualitative approach with oriented on "qualitative descriptive" (Qualitative Desciptive Design). The result of the research explains that: (1) the learning process of PAI based on culture and character of the nation in SMA Negeri 3 in Yogyakarta through integrated learning by teachers with students actualized on religious values and tolerance, including: the value of faith, the practice of worship to Allah, and social activities (2) that integrated learning by PAI teachers results in the cultural and character values that students exhibit in their religious and tolerant attitudes, such as the character of faith that is actualized in performing worship worship, manners in behavior and speech, peer empathy, (3) PAI learning process with model reform and material cotectualization (integrated domain) can improve the knowledge, attitude, and behavior of students through the cultivation of creative value and responsibility of students in their life, and (4) The practice of practicing the students' worship is shown Through the implementation of "worship maghdoh", such as: prayer, fasting, and reciting the Qur'an, and worship "ghoiru maghdoh" (social-community worship), such as: social-community activities, love environment, and tolerance.